2009
DOI: 10.1016/j.virol.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A single point mutation in E2 enhances hepatitis C virus infectivity and alters lipoprotein association of viral particles

Abstract: Hepatitis C virus (HCV) infection is a major worldwide health problem. Our previous results showed that HCV evolved to gain the enhanced infectivity and altered buoyant density distribution during persistent infections in vitro. Here we showed that a point mutation I414T in HCV E2 was mainly responsible for these phenotypic changes. While the I414T mutation had no significant effect on HCV RNA replication and viral entry, it enhanced the production of infectious viral particles and decreased the dependency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 43 publications
5
49
0
Order By: Relevance
“…4). Envelope mutations with similar effects on SR-BI dependency and neutralization susceptibility have been reported by others (49)(50)(51), suggesting that these mutations also might be linked to the role of HVR1 in entry. Overall, it seemed that dependency on both lipoprotein receptors, SR-BI and LDLr, was either indirectly or directly linked with the role of HVR1 in viral entry, whereas dependency on CD81 was not.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…4). Envelope mutations with similar effects on SR-BI dependency and neutralization susceptibility have been reported by others (49)(50)(51), suggesting that these mutations also might be linked to the role of HVR1 in entry. Overall, it seemed that dependency on both lipoprotein receptors, SR-BI and LDLr, was either indirectly or directly linked with the role of HVR1 in viral entry, whereas dependency on CD81 was not.…”
Section: Discussionsupporting
confidence: 74%
“…A ratio of transfected to naive Huh7.5 cells of 1:150 was used for cells plated in standard medium, and a ratio of 1:30 was used for cells plated in standard medium supplemented with 10 g/ml of the cross-genotype-reactive HCV neutralizing antibody AR3A (37). This concentration of AR3A represented at least 500 times the 50% inhibitory concentration (IC 50 ) for the tested HVR1-deleted viruses (data not shown). Six replicates of cell mixtures from each virus recombinant were plated in the absence or presence of AR3A for fixation at three time points: 24 h, 48 h, and 72 h postplating.…”
Section: S29 Cell Transfectionmentioning
confidence: 97%
“…HCVcc (JFH1 strain, genotype 2a) (GenBank accession number AB047639) (46,47) was used in these studies. The protocols for the generation of HCVcc or HCVΔE1, including in vitro RNA transcription and electroporation, were described previously (18,33,47).…”
Section: Methodsmentioning
confidence: 99%
“…Through their C-terminal transmembrane domains (TMDs), E1 and E2 form a stable noncovalent heterodimeric complex that mediates virus entry and determines viral pathogenicity and the host immune response (13)(14)(15). The HCV envelope proteins may also mediate the association of viral particles with host low-density lipoprotein (LDL) or very-low-density lipoprotein (VLDL), which plays important roles in virus entry, egress, and evasion of the host immune response (12,(16)(17)(18). E2 contains the major viral structural elements that are responsible for binding to host receptors, including CD81 and scavenger receptor class B type I (SR-BI) (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…These proposed mechanisms include genetic escape (61), the occlusion of neutralizing epitopes through glycan shielding (18,26) and lipid associations (23,54), infection enhancement via serum components such as high-density lipoprotein (HDL) and apolipoproteins (13,14,60), and cell-to-cell transmission (7,63). An additional mechanism was recently proposed by Zhang and colleagues, who reported that a linear region of E2 encompassing amino acids 434 to 446 (the so-called epitope II) elicits nonneutralizing antibodies in humans and chimpanzees that can inhibit the neutralizing activity of antibodies targeting aa 412 to 423 (65,66).…”
mentioning
confidence: 99%